Isolation and evaluation of proteins from fermented Lupinus angustifolius flour for food applications - Coorey, R.; Ho, M.; Jayasena, Vijay (2011)
Fermentation parameters for lupin (Lupinus angustifolius) flour, cv. Kalya, and commercially available flour were determined using the food grade mould, Rhizopus oligosporus. Under optimum fermentation conditions: 56 h incubation time at 28°C, with 50% deionised water and 4 g/kg R. oligosporus level, lupin flours formed compact tempe-like cakes covered with mycelia growth. Fermentation lowered the ash and the extractable protein contents. Crude protein content remained unchanged. Significant increase in the foaming capacity was found for protein isolates from both fermented flours. Fermentation had detrimental effects on emulsifying properties. Extracted protein isolates from both fermented flours were found to fit best in a model food system based on a meat patty formulation. The potential of fermented lupin flour as a protein source in functional foods is promising.